(untitled) - Clark, Maxine K. (Hoboken, N.J., 2006)
Build-A-Bear Workshop® is one of the most successful retailing concepts in recent history. Starting with just one location in 1997, the company now operates more than 200 stores worldwide. Leading the way is Maxine Clark, the company's founder, Chairman, and Chief Executive Bear. Clark is widely recognized as one of the nation's leading and most creative entrepreneurs. In The Bear Necessities of Business, she reveals how she built this amazing global business from the ground up, while arming you with the tools you need to start, run, and market your own company in today's tough competitive environment. While primarily drawing on real-life experiences from Build-A-Bear Workshop®, Clark also offers wisdom gained throughout her entire thirty-plus-year career, including lessons and examples from some of the other great companies that do so much right. Straightforward and accessible, The Bear Necessities of Business is divided into seven parts, each built around an essential element that will allow you to stand apart from the crowd. The short, accessible chapters show you everything you need to: * Get your business started * Become a great boss * Connect with your customers * Add value to the overall experience * Effectively market your company * Plan for future growth * Give back to your customers, employees, and community Best of all, these principles can be applied to any industry and are proven to work whether your target audience is children, teenagers, baby boomers, seniors, or any age in-between. Whether you're looking to start a new business, improve an existing one, be a better manager, or hire the best employees, The Bear Necessities of Business contains the insights and information you need to succeed. Even if you work for some-one else and have no plans to strike out on your own, you'll still benefit from the advice found in this book. After all, the best employees—and those who consistently rise to the top—are those who think like entrepreneurs!
Keywords: New business enterprises,Entrepreneurship,Doanh nghiệp kinh doanh mới,Kinh doanh